2017
DOI: 10.3390/s17040662
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Monitoring of Green Roof Vegetation Health State in Sub-Mediterranean Climate: Preliminary Results

Abstract: In urban and industrial environments, the constant increase of impermeable surfaces has produced drastic changes in the natural hydrological cycle. Decreasing green areas not only produce negative effects from a hydrological-hydraulic perspective, but also from an energy point of view, modifying the urban microclimate and generating, as shown in the literature, heat islands in our cities. In this context, green infrastructures may represent an environmental compensation action that can be used to re-equilibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The spectral indices analyzed from the reflectance values reflect the health status of leaves, which is mostly influenced by environmental factors, developmental factors, physical factors, and biochemical factors, in which the chemical constituents play a major role in the physiological state of the leaves . In this study, two specific indices, namely, narrowband and broadband indices, are used to estimate the stress level of plants . Narrowband indices represent specific wavelengths linked to plant pigments, and changes in the values are related to the health status of the plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral indices analyzed from the reflectance values reflect the health status of leaves, which is mostly influenced by environmental factors, developmental factors, physical factors, and biochemical factors, in which the chemical constituents play a major role in the physiological state of the leaves . In this study, two specific indices, namely, narrowband and broadband indices, are used to estimate the stress level of plants . Narrowband indices represent specific wavelengths linked to plant pigments, and changes in the values are related to the health status of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…19 In this study, two specific indices, namely, narrowband and broadband indices, are used to estimate the stress level of plants. 20 Narrowband indices represent specific wavelengths linked to plant pigments, and changes in the values are related to the health status of the plant. Broadband indices are based on specific wavelengths associated with green, red, visible, and NIR regions, which reveals the metabolic response during development and under stress conditions (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of plants in a healthy and unhealthy state for the three species monitored in this study (not shown) highlighted that spectral signatures of plants in a healthy state presented the characteristic behaviour of vegetation described in Reference [20] and briefly described in the introduction. In Reference [25], a preliminary investigation of the trend of a limited number of vegetation indices within the monitoring period for all the species under investigation is presented. All trends revealed an initial suffering period (December 2014-March 2015) after which the vegetation health improved.…”
Section: Resultsmentioning
confidence: 99%
“…To this aim, the field-portable spectroradiometer FieldSpec 4-ASD was employed. For a detailed description of the site under investigation and data acquisition refer to References [13,25], respectively. Within the monitoring period (December 2014-June 2015) two canopies of each plant species, for a total of six plants, were monitored.…”
Section: Case Study: University Of Calabria's Green Roofmentioning
confidence: 99%
See 1 more Smart Citation